PERLINDUNGAN HUKUM DAN HAK WARIS ANAK ANGKAT: STUDI KOMPARATIF HUKUM ISLAM, HUKUM PERDATA, DAN HUKUM ADAT - Amran Nani; Mujibur Rachman Kautjil; Tamam Maliya; Djunaidi Usia (Fasya UIN Sultan Aji Muhammad Idris Samarinda, 2026)
Child adoption is a common social phenomenon in Indonesia. However, the plurality of legal systems applicable in Indonesia namely Islamic Law, Civil Law, and Customary Law gives rise to significantly different legal implications regarding the inheritance rights and legal status of adopted children. This study employs a normative juridical method using a comparative legal approach. The findings indicate that under Islamic Law, adoption does not sever the biological relationship between the adopted child and the biological parents. Consequently, an adopted child is not entitled to inherit ab intestato, but may receive a compulsory bequest (wasiat wajibah) of up to one-third of the estate. In contrast, Civil Law recognizes the legal severance of the relationship with the biological parents, granting the adopted child the status of a legitimate child and placing them among the first-class heirs. Meanwhile, Customary Law varies considerably across regions. In Java and Bali, adoption may transfer the child's status as an heir, whereas in strictly patrilineal societies such as the Batak community, adopted daughters face limitations in inheritance rights. This legal diversity requires a reconstructive understanding to ensure legal certainty and the protection of children's rights in Indonesia.